THE INFLUENCE OF VILLAGE FUND BUDGET AND MALANG DISTRICT ECONOMIC DEVELOPMENT ON VILLAGE INCOME BASED ON PMK NUMBER.205/PMK.07/2019 (CASE STUDY OF SAWAH PUJON KIDUL CAFE TOURIST DESTINATION) - Shella Wati Fauzi; Fatimah Riswati (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
A tourism village is a form of integration between attractions, accommodation and supporting facilities that are presented in a structure of community life that is integrated with the prevailing procedures and traditions. Pujon Kidul is one of the villages that has successfully implemented a tourism village development program with the destination of Cafe Sawah. This research aims to examine and analyze the effect of the village budget and the development economy of Malang Regency on village income. The number of samples in this research were 70 people who were taken from visitors and business actors in the tourist destination area of ​​Cafe Sawah Pujon Kidul, using non-probability sampling techniques, with accidental sampling method. Collecting data using primary data sources through distributing questionnaires. Data analysis was carried out using statistics with the SPSS version 21 application. The research method used was a quantitative approach. Based on the hypothesis test of village funds and economic development, partially and simultaneously have a positive and significant effect on village income. So it can be concluded that the results of this research show that village funds and economic development that are managed and supervised by the village government and the Pujon Kidul community are proven to increase the income of Pujon Kidul village.